Reconstruction of fish allergenicity from the content and structural traits of the component β-parvalbumin isoforms - Pérez-Tavarez, Raquel; Carrera, Mónica; Pedrosa, María; Quirce, Santiago; Rodríguez-Pérez, Rosa; Gasset, M. (Scientific Reports, 2019)
12 pages, 7 figures.-- This article is licensed under a Creative Commons Attribution 4.0 International License Most fish-allergic patients have anti-β-parvalbumin (β-PV) immunoglobulin E (IgE), which cross-reacts among fish species with variable clinical effects. Although the β-PV load is considered a determinant for allergenicity, fish species express distinct β-PV isoforms with unknown pathogenic contributions. To identify the role various parameters play in allergenicity, we have taken Gadus morhua and Scomber japonicus models, determined their β-PV isoform composition and analyzed the interaction of the IgE from fish-allergic patient sera with these different conformations. We found that each fish species contains a major and a minor isoform, with the total PV content four times higher in Gadus morhua than in Scomber japonicus. The isoforms showing the best IgE recognition displayed protease-sensitive globular folds, and if forming amyloids, they were not immunoreactive. Of the isoforms displaying stable globular folds, one was not recognized by IgE under any of the conditions, and the other formed highly immunoreactive amyloids. The results showed that Gadus morhua muscles are equipped with an isoform combination and content that ensures the IgE recognition of all PV folds, whereas the allergenic load of Scomber japonicus is under the control of proteolysis. We conclude that the consideration of isoform properties and content may improve the explanation of fish species allergenicity differences This work was supported by grants from the Spanish AEI/EU-FEDER SAF2014-52661-C3 (MG) and BFU2015- 72271-EXP (MG), Angulas Aguinaga (MG, RRP) contract and the Ramón Areces Foundation (MC). MC is a Ramón y Cajal fellow Peer reviewed